Peran UTAUT2 dan Satisfaction terhadap Behavioral Intention pada Platform Freemium - Ratu Aulia Kinanti; Ryna Parlyna; Inkreswari Retno Hardini (Indo Publishing, 2026)
The rapid development of the video streaming industry has become increasingly competitive, prompting service providers to implement freemium business models through free trial offerings to attract new customers. This study aims to analyze the effect of Performance Expectancy, Price Value, and Hedonic Motivation on Behavioral Intention, both directly and through the mediation of Satisfaction in the context of the YouTube Premium free trial service. This research employs a quantitative explanatory approach using a survey method. Sampling was conducted using a purposive sampling technique, involving 150 respondents who are YouTube Premium free trial users residing in the DKI Jakarta Province. Primary data were collected through an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results of the hypothesis testing indicate that Performance Expectancy, Price Value, Hedonic Motivation, and Satisfaction have a positive and significant effect on Behavioral Intention. Furthermore, the mediation analysis proves that Satisfaction plays a complementary partial mediation role in the relationship between Performance Expectancy, Price Value, Hedonic Motivation, and Behavioral Intention. The findings of this study indicate that although user satisfaction and pleasure are exceptionally high during the trial period, economic value rationality and functional fulfillment remain the dominant factors driving the conversion decision to a paid subscription, particularly among consumers in developing countries. Practically, this research recommends that streaming service providers focus not only on the entertainment experience but also maintain competitive pricing strategies and high-quality premium features to optimize customer retention rates.